Bacteriological profile and antibiotic susceptibility pattern of Neonatal Septicemia in Kanti Children Hospital, Nepal - Deepeshwara Nepal; Sumit Agrawal; Sushan Shrestha; Ajit Rayamajhi (Journal of Gandaki Medical College, 2020)
Background: Neonatal sepsis is one of the major causes of neonatal morbidity and mortality globally. Current neonatal mortality rate of Nepal is 21/1000 live birth which is higher than that of the global average of 19.2 and slightly lower than the regional (South East Asia). Pathogenic strains of neonatal sepsis varies from place to place and also from time to time, so it is very important to know the common pathogens and its resistant pattern locally. The aim of this study is to find out the hospital based frequency of neonatal sepsis and characterize the bacteriological profile along with their sensitivity and resistance pattern.